2013
DOI: 10.2174/1573406411309060003
|View full text |Cite
|
Sign up to set email alerts
|

QSAR and Docking Studies of HCV NS3 Serine Protease Inhibitors

Abstract: Hepatitis C virus (HCV) is a Hepacivirus that causes chronic liver disease, leading to hepatocellular carcinoma, cirrhosis, and chronic hepatitis in about 3% of the world population. In this study, novel HCV NS3 serine protease inhibitors based on 93 boceprevir analogs were studied by QSAR analyses using thermodynamic, structural and topological descriptors, including E-state descriptors. Novel compounds were proposed using the QSAR models. Both models were highly predictive, with calibration, leave-one-out va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…A few regression based studies have been reported to identify inhibitors against HCV NS3 drug target [45] , [19] . Lafridi et al 2022 used the QSAR based Multiple Linear Regression (MLR) approach to study the interaction between macrocyclic inhibitors and NS3 protease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few regression based studies have been reported to identify inhibitors against HCV NS3 drug target [45] , [19] . Lafridi et al 2022 used the QSAR based Multiple Linear Regression (MLR) approach to study the interaction between macrocyclic inhibitors and NS3 protease.…”
Section: Discussionmentioning
confidence: 99%
“…da Cunha et al, 2013 developed QSAR based models using 93 boceprevir analogs achieving the R 2 of 0.66 for NS3 protease. They also performed molecular docking of promising analogs for binding affinity to NS3 protease [19] . In addition, we found a classification based method using 413 NS3 protease inhibitors having Matthew's correlation coefficient (MCC) of 0.79 [46] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The QSAR (quantitative structure activity relationship) is considered a widely used computational technique to construct prediction models which can distinguish the impact of important molecular fingerprints regulating their bioactivities and properties [19]. A variety of targets, including antioxidant [20], antibacterial [21,22], anticancer [23,24], and antiviral [25,26] activities, have been successfully modeled using QSAR models.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Quantitative structureactivity/property relationship (QSAR/QSPR) is a commonly used computational technique for building predictive models that can discern the influence of significant molecular descriptors governing their biological activities and chemical properties. [16,19] Such QSAR models has been successfully employed for modeling a wide range of targets such as, antioxidant, [20][21][22] antimicrobial, [23][24][25][26] anticancer, [27,28] and antiviral [29,30] activities. As such, owing to the beneficial functions of QSAR models, herein, a large number of HCV inhibitors were used as the data set for the development of predictive models to facilitate rational drug design.…”
Section: Introductionmentioning
confidence: 99%